Twelve months : a novel of the Dresden files - Butcher, Jim, 1971- (Butcher, Jim, 1971- Dresden files, 2026)
"Harry Dresden, Chicago's only professional wizard, has always managed to save the day--but, in this powerful entry in the #1 New York Times bestselling Dresden Files, can he save himself? One year. 365 days. Twelve months. Harry Dresden has been through a lot, and so has his city. After Harry and his allies narrowly managed to save Chicago from being razed to the ground, everything is different--and it's not just the current lack of electricity. In the battle, Harry lost people he cared about. And that's the kind of loss that takes a toll. Harry being Harry, he's doing his level best to help the city and his friends recover and rebuild. But it's a heavy load, and he needs time. But time is one thing Harry doesn't have. Ghouls are prowling Chicago and taking out innocent civilians. Harry's brother is dying, and Harry doesn't know how to help him. And last but certainly not least, the Winter Queen of the Fae has allied with the White Court of vampires--and Harry's been betrothed to the seductive, deadly vampire Lara Raith to seal the deal. It's been a tough year. More than ever, the city needs Harry Dresden the wizard--but after loss and grief, is there enough left of Harry Dresden the man to rise to the challenge?"--